High cardiorespiratory fitness is inversely associated with incidence of overweight in adolescence: a longitudinal study - Savva, Savvas C.; Tornaritis, Michael J.; Kolokotroni, Ourania; Chadjigeorgiou, Charalambos; Kourides, Yiannis A.; Karpathios, Themistocles; Yiallouros, Panayiotis K. (My University, 2014)
To assess the association of baseline cardiorespiratory fitness (CRF) with incidence of overweight over a 4.6-year period in adolescence. In a cohort of 4878 adolescents, we assessed body mass index in years 2001-2003 and 2007. CRF was assessed at baseline as maximal oxygen consumption (VO2max, mL/kg/min) using the 20-m shuttle run test and was examined against incidence of overweight at follow-up. Estimated VO2max at baseline was higher in males than in females, P<0.001, and was lower in overweight and obese than in non-overweight subjects. The incidence of overweight at follow-up among non-overweight participants at baseline was 15.5% [95% confidence interval (CI) 13.7% to 17.3%] in males and 5.6% (95% CI 4.9% to 7.0%) in females, P<0.001. Adjusted odds ratio for incidence of overweight in participants in the fourth quartile of VO2max was 0.40 (95%CI 0.26 to 0.61) in males and 0.57 (95% CI 0.33 to 0.99) in females in comparison with participants in the first quartiles of VO2max. Incidence of overweight was three times more frequent in males than in females. Among non-overweight at baseline, high fitness levels were inversely associated with incidence of overweight at follow-up, suggesting that interventions aiming to increase CRF in early childhood might help reverse increasing trends in obesity.
Keywords: Cardiorespiratory fitness; Obesity; Overweight; Adolescence